The Role of SPADA as Instructional Media and Technologies to Utilize Learners’ Self-Regulated Learning - Welliam Hamer; Ledy Nur Lely (Journal of English Education Studies, 2020)
The aim to be reached in writing this article is to inform the readers on how SPADA as one of instructional media based technologies today is effective to increase the quality of the learners in their self-regulated learning. In recent years, technology has increasingly developed with its widespread use in the economy, tourism and even education in the world. The existance of technology-based media in teaching and learning activities is needed to accompany the increasingly modern era of globalization. One of the technology-based media used in education is e-learning media. E-learning is a type of teaching and learning that allows the delivery of teaching materials to learners using the internet, intranet or other computer network media (Hartley, 2001). With this technology-based media, teaching and learning activities that previously only took place on campus or school, can be conducted anywhere and anytime, not limited by space and time. One of the e-learning media on campus is SPADA (Online Learning System). This system is developed to answer some of the challenges of higher education and organize learning without limits. The use of the SPADA website as a utilization of learners' self integration means how the use of SPADA can facilitate learners to practice their self-regulated learning. It means that by using SPADA, the learners are expected to increase their learning activities autonomously. By doing so, the lecturers/teachers only need to give their learners the lesson materials and perhaps some assignments then the rest of learning process will be left entirely to the learners, giving them freedom to pick their own learning pace. In this case, SPADA as one of instructional media based technologies is effective to improve the quality of the learners’ self-regulated learning.